Human capital: challenges for Russia - Vladimir Mau (Publishing House Delo, 2013)
The development human capital is now recognized as being the most important precondition of economic growth in modern times. It should be a priority in our socio-economic policy. However, recognition of this fact alone will not produce a qualitative leap in the development of education, healthcare and the pension system. We need fundamental changes in these sectors if they are to become capable of meeting the challenges of post-industrial society. This will mean individualization of the services provided, continuous delivery of these services (over the lifetime of an individual), privatization (an increase in the role of private funding), the internationalization of competition and implementation of the latest technologies in the delivery of services. – – . , ( , ), . . -, , . , — , .
Keywords: E24; G23; H75; I15; I18; I25; I28; 330; socioeconomic policy; pension system; healthcare; human capital; education